Anatomical considerations in bronchoscopy - Ryan, Brienne; Yendamuri, Keerti; Yendamuri, Sai (Journal of Thoracic Disease; Vol 9, Supplement 10 (September 12, 2017): Journal of Thoracic Disease (Interventional Pulmonology), 2017)
A thorough understanding of intrathoracic anatomy enables the interventional bronchoscopist to perform procedures efficaciously. The review of the anatomy of the thoracic cavity focuses first on the trachea and the relationship of the airway with surrounding structures, knowledge important for the safe conduct of bronchoscopic procedures. We then describe the anatomy of the pleural cavity relevant to the practitioner performing pleuroscopy.